Familiarity, Expertise, and Change Detection: Change Deafness is Worse in Your Native Language. (February 2014) - Neuhoff, John G; Schott, Steven A; Kropf, Adam J; Neuhoff, Emily M
We first replicated the language-familiarity effect for voice discrimination and found better voice discrimination in familiar languages. However, when listeners were not cued to listen for changes, both English and Spanish speakers exhibited greater change deafness in their familiar language. Results suggest that lexical/semantic attention in a familiar language and increased indexical processing in an unfamiliar language can produce greater change deafness in familiar languages.